Cothay Manor
Nor was the Bishop of Salisbury alone in defending his hearth and home. Richard Bluett in 1481 rebuilt his former house to withstand civil war by the addition of a moat and gatehouse. Many properties outside the towns had been claimed by more powerful neighbors, and gentlemen's estates, now that the pillaging of France was at an end, were particularly tempting.